Main areas detection on tennis courts (2021)
ABSTRACT : This paper is going to show all the ETL process, which includes obtaining of the images, label process of images of tennis matches with the objective of detecting the main areas of the court. The process continues with the generation of a baseline using a heuristic process and the generation of a deep learning model, with modification on the characteristics of the images, that allows the detection of main areas on the tennis courts, as well as the pick of the best option for the task selected, based on their performance.